2016
DOI: 10.1038/srep22325
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ regulates Treg cell fate and promotes allograft survival via a systemic IL-10 production that is CD4+ CD25+ Foxp3+ T cells independent

Abstract: CD4+ CD25+ Foxp3+ Tregs have been shown to play a central role in immune homeostasis while preventing from fatal inflammatory responses, while Th17 cells have traditionally been recognized as pro-inflammatory mediators implicated in a myriad of diseases. Studies have shown the potential of Tregs to convert into Th17 cells, and Th17 cells into Tregs. Increasing evidence have pointed out CD25 as a key molecule during this transdifferentiation process, however molecules that allow such development remain unknown.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 46 publications
4
60
0
1
Order By: Relevance
“…(23) More importantly, IFN-γ producing cells that co-express IL-10 have displayed immunosuppressive properties. (24) We therefore focused on the effects of TAC on old CD4 + T cells and tested whether the observed prolongation of graft survival in old mice was linked to a modified balance of IFN-γ and IL-10 production by CD4 + T cells. Old and young mice underwent fully MHC-mismatched skin transplants and systemic IFN-γ and IL-10 production was quantified by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(23) More importantly, IFN-γ producing cells that co-express IL-10 have displayed immunosuppressive properties. (24) We therefore focused on the effects of TAC on old CD4 + T cells and tested whether the observed prolongation of graft survival in old mice was linked to a modified balance of IFN-γ and IL-10 production by CD4 + T cells. Old and young mice underwent fully MHC-mismatched skin transplants and systemic IFN-γ and IL-10 production was quantified by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, double-positive CD4 + IFN-γ + IL-10 + cells also termed regulatory type 1 cells display potent immunosuppressive properties and are able to promote allograft survival independently of CD4 + CD25 + Foxp3 + regulatory T cells. (24) Thus, altering the critical balance of IFN-γ and IL-10 may play a pivotal role in mediating age-specific effects of Tacrolimus. (32,35)…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, WT mice treated with NAD + exhibited 100% survival while casp-11 -/mice treated with PBS exhibited a modest 40% survival, suggesting that NAD + promotes survival beyond non-canonical inflammasome blockade. Our previous studies have delineated the effects of NAD + on various immune cells such as dendritic cells and CD4 + T cells including Th1, Th17, regulatory type 1 (Tr1) and Treg cells communicated exclusively through mast cells (MCs) [15][16][17] . Thereby, NAD + treatment promoted MC derived induction of TR1 cells that resulted into increased systemic levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…3C). Moreover, we have previously shown that NAD + administration dampens the expression and activation of transcription factors such as STAT-5 16 .…”
Section: Nad + Inhibits the Non-canonical Inflammasome Through Stat-1mentioning
confidence: 97%
See 1 more Smart Citation